The Impact of Foreign Defense Aid on the Fight Against Insurgency in Northern Nigeria - Dauda, Khalid Iliyasu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Terrorism is one of the major challenges states face globally. The importance of this problem creates strong incentives for policymakers to design efficient counter insurgency policies. From the global north to the global south, terrorism has become a reality of the modern world. Developing countries are more vulnerable because they lack the technical expertise to handle this imminent threat. As a result, policymakers of most Western democracies employed the idea of providing defense aid to increase their capabilities towards preventing and combating insurgencies. Although fighting insurgency by foreign defense aid continues to find resonance in the policy circles, academics are more skeptical of this policy. Since 2009, Boko Haram has remained the biggest security threat in Nigeria. The group challenges the sovereignty of the country in the course of promoting Islamic revivalism. The military began to face a new paradigm of conflict (non-conventional warfare). The country lacks the technical expertise and financial capacity to produce the necessary equipment for the military. Subsequently, the government sought aid from friendly countries like the United States and the United Kingdom. However, the lingering insurgency in northern Nigeria has prompted the need for questions to be asked. What has been the outcome of the defense aid? This research work delves into the impact of foreign defense aid on Nigeria’s war against insurgency. The question guiding this study is how effective has Nigeria’s use of foreign defense aid been in the fight against insurgency? Keywords: Insurgency, Terrorism, Foreign Defense Aid, Boko Haram.

ÖZ:Terörizm, devletlerin küresel olarak karşılaştığı en büyük zorluklardan biridir. Bu sorunun önemi, politika yapıcılar için etkili isyan karşıtı politikalar tasarlamaları için güçlü teşvikler yaratır. Küresel kuzeyden küresel güneye terörizm, modern dünyanın bir gerçeği haline geldi. Gelişmekte olan ülkeler, bu yakın tehdidi ele alacak teknik uzmanlığa sahip olmadıkları için daha savunmasızdır. Sonuç olarak, çoğu Batı demokrasisinin politika yapıcıları, isyanları önleme ve bunlarla mücadele etme yeteneklerini artırmak için savunma yardımı sağlama fikrini kullandılar. Dış savunma yardımı ile isyanla mücadele politika çevrelerinde yankı bulmaya devam etse de, akademisyenler bu politikaya daha şüpheyle yaklaşıyor. Boko Haram, 2009'dan beri Nijerya'daki en büyük güvenlik tehdidi olmaya devam ediyor. Grup, İslami uyanışı teşvik etme sürecinde ülkenin egemenliğine meydan okuyor. Ordu, yeni bir çatışma paradigmasıyla (konvansiyonel olmayan savaş) karşı karşıya gelmeye başladı. Ülke, ordu için gerekli teçhizatı üretecek teknik uzmanlığa ve mali kapasiteye sahip değil. Daha sonra hükümet, Amerika Birleşik Devletleri ve Birleşik Krallık gibi dost ülkelerden yardım istedi. Ancak, kuzey Nijerya'da süregelen isyan, soruların sorulması ihtiyacını doğurdu. Savunma yardımının sonucu ne oldu? Bu araştırma çalışması, yabancı savunma yardımının Nijerya’nın isyana karşı savaşı üzerindeki etkisini araştırıyor. Bu çalışmaya rehberlik eden soru, Nijerya’nın dış savunma yardımını kullanmasının isyanla mücadelede ne kadar etkili olduğudur? Anahtar Kelimeler: İsyan, Terörizm, Dış Savunma Yardımı, Boko Haram.
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2021. Supervisor: Asst. Prof. Dr. Nuray Ibryamova.
Keywords: Nigeria-Foreign Relations; Insurgency-Nigeria; Boko HaramxTerrorism zNigeria; Violence-Nigeria-Religious aspects; Politics and government-Nigeria; Islamic fundamentalism-Nigeria; Insurgency; Terrorism; Foreign Defense Aid; Boko Haram